Compter des buts en lisant : une validation des programmes Blizzlecture et Raplecture pour accroitre la motivation à lire - Mazerolle, Marie-Pier; Long, Marie-Josée; Bossé-Perron, Lisa; Roy-Charland, Annie (Canadian Journal of Education/Revue canadienne de l'éducation, 2025)
To meet the needs of young people lacking motivation, the use of role models can be a strategy for fostering identity building and encouraging positive relationships with reading. In fact, boys, who often show lower motivation for this activity, could benefit from being mentored by male role models. The aim of the present study was to validate the effectiveness of a community-based literacy program focused on improving reading motivation using positive role models: local hockey players. One hundred and twenty-four students were divided into an experimental group (following the program for 10 to 12 weeks) and a control group, completing questionnaires (self-efficacy, self-esteem, reading motivation) at a pre- and post-test. Results show that students in the Blizzlecture and Raplecture programs experienced a decrease in reading motivation due to guilt, which was not observed in the control group. The results highlight the effectiveness of the programs in reducing less self-determined motivations, essential for the development of intrinsic motivation.